Evaluation of pre- and in-hospital workflows and time intervals with acute ischemic stroke patients - Mikko Helander; Timo Iirola; Pauli Ylikotila; Hilla Nordquist (PLoS ONE, 2025)
Objective Stroke is one of the leading causes of death and disability globally. Rapid recanalization therapy for acute ischemic stroke (AIS) patients is critical for improving outcome. While in-hospital time intervals have decreased and treatment methods have improved over the past decade, pre-hospital time intervals have remained unchanged. This study aims to develop a comprehensive understanding of the prognosis of AIS patients based on pre-hospital and in-hospital data. Methods A retrospective study was conducted in Southwest Finland covering the period of 01/01/2022-31/12/2022. The study included a total of 174 AIS patients who were conveyed by the emergency medical services (EMS) to Turku University Hospital (TUH) and given intravenous thrombolysis (IVT) and/or endovascular treatment (EVT). Pre- and in-hospital care records of AIS patients were analyzed to evaluate workflows, time intervals, and the impacts of these time intervals on patient outcome. Binary logistic regression analysis was utilized to identify predictors of on-scene time (OST) and favorable outcome. Results The median OST for EMS was 19 minutes. Analysis indicated that the scene of the stroke event being an apartment building, barriers to care such as a locked door, vertigo as a symptom, and EMS taking measurements on-scene were predictive of longer OST. Longer OST was observed to negatively impact patient outcome, along with symptom severity and gender. Using the stroke code as the dispatch code and positive FAST signs were associated with shorter OST. In-hospital median door to needle time (DNT) was 14 minutes in the IVT group and 11 minutes in the IVT+EVT group. EMS prenotification was associated with shorter in-hospital time intervals. Conclusions The presence of vertigo as a symptom poses challenges to identification by EMS. Pre-hospital OST meets national targets, but EMS workflows could be optimized to reduce OST and thereby positively influence patient outcome. These findings underscore the need for targeted interventions in EMS protocols to improve stroke care outcomes.